Vorschläge zur kartographischen Darstellung der Industrie in großen, mittleren und kleinen Maßstäben - Wenzel, Alfred (ERDKUNDE, 1971)
The following facts play an important role in the cartographic representation of industry: the collection and applicability of relevant industrial statistical data; the way in which figures can be used as pictorial overlay material; and the ability to centre figures on the actual location; the large range between maximum and minimum values and a strong division in depth of industrial classification. In the latter case the industrial groupings defined in the maps of the German Land Planning Atlases have been found useful. Using these industrial groupings as a basis, a colour key for all scales was developed. Using the example of the town of Alfeld at a scale of 1 : 5,000, industrial premises are shown in a darker tone, and industrial land with storage areas and rail sidings in a lighter tone, of the same colour. At the 1 : 25,000 scale, coloured divided circles, proportional in area to the number of employees were laid over the industrial buildings, while the total industrial land use area of the town was shown in yellow. Using the example of the Upper Franconian industrial area, at a scale of 1 : 100,000 the size of plant at each location was represented, in terms of a progression from small, medium, large to very large by a circle and ring symbol. To make interpretation easier, all the indicators of the structure of medium size and very large plants were given one or two additional thin outer rings. The proportion of employed persons in productive trade and industry in the communes and cities is shown by coloured bar graphs. At a scale smaller than 1 : 300,000 it was only possible to show plants with more than or less than 200 employees by dominant industrial groupings. In this situation the symbols which indicate less than 200 employees at any one location were given an additional thin circle. At a scale of 1 : 500,000 the basis for delimiting the areas of influence of individual industrial groupings was devised. All plants with 200 or more employees at one location were represented quantitatively by proportional circles in a darker colour. After subtracting the employees thus accounted for from total employment, the dominant industrial grouping among remaining employment is shown qualitatively by colouring the administrative area of the commune in a lighter tone. After comparing the scatter of similarly coloured commune areas and the quantitatively represented industrial plants of the same industrial grouping, the 1 : 1,000,000 map, based on commune areas, give a generalised delimitation of the area of influence of an industrial grouping centred on dominant locations. The areas thus delimited are distinguished by a lighter colour corresponding to the industrial grouping. By means of such a presentation the difference between the labour-intensive textile and clothing industry with predominantly small and medium size plants and the labour-intensive ceramics and glass industry with predominantly large and very large plants was clearly expressed. In large scale industrial maps the problems lie more on the side of obtaining suitable data than on the cartographic and technical side. This last aspect is strongly evident in the medium scales, while on the small scales cartographic and technical problems fade into the background, only to be replaced by questions relating to the subject matter under study. In this connection the elucidation of spatial and sectoral linkages is important. Certain dominant types of industrial structure or industrial formations can be recognised and their complex areas of influence cartographically fixed. This was undertaken for the example of the Rhine Westphalian industrial area, historically based on coal, at a scale of 1 : 1,000,000. The various industrial areas were distinguished by diagonal hatching leftwards and to the right and by grey stippling on the lighter colour for iron, steel and non-ferrous metallurgy, and it was possible to identify the locational bases in coal-, ore- and transport oriented areas. Using the same graphical means of expression as for the differentiation of heavy industrial areas on a locational basis, it is possible to further differentiate the various areas of influence of industrial groupings designated by lighter colouring, at a scale of 1 : 1,000,000 and smaller and to raise the level of explanation by explanatory material in the key.